Eş’ariyye ve Mu’tezile’nin tevhîd anlayışının mukayesesi - Güney, Züleyha (My University, 2010)
tezile, Eş’ariyye, Allah’ın sıfatları, tevhîd, halk’ul-Kur’ân, ru’yetullah ÖZET EŞ’ARİYYE VE MU’TEZİLE’NİN TEVHÎD ANLAYIŞININ MUKAYESESİ İslâm dininin temel prensibi tevhîddir. Bundan dolayı İslâm düşünürlerinin ilk gayesi Allah’ın varlığını ve birliğini ortaya koymaya çalışmaktır. İslâm düşüncesinde tevhîd meselesi üzerinde titizlikle duran iki ekol vardır. Bunlardan biri Ehl-i Sünnet, diğeri ise Mu’tezile’dir. Mu’tezile tevhîd başlığı altında Allah’ın sıfatları, Kelâmullah ve ru’yetullah konularında görüş beyan etmiştir. Allah’ın sıfatları beşerin sıfatlarına benzemez. Allah’a mahsus en özel sıfat O’nun kadim olmasıdır. Bundan dolayı Mu’tezile, Allah’a mahsus diğer zâti sıfatları te’vil etme yolunu tercih etmiştir. Mu’tezile Allah’ın kelâmının ses ve harflerden oluştuğunu bu nedenle Kur’an-ı Kerim’i de hâdis kabul etmek gerektiğini savunmuştur. Ru’yetullah konusunda da Allah’ın hem dünyada hem de ahirette görülemeyeceğini söylemiştir. Eş’ariyye ise, ilahi sıfatları ispat etmiş ve bunların Allah’ın zâtıyla kâim olan ezelî sıfatları olduğunu söylemiştir. Halk’ul-Kur’ân konusunda Kur’ân’ın mânası yani lafızlardan soyutlanmış olan aslı ezelî, lafızları ise mahlûktur görüşünü benimsemiştir. Eş’ariyye’ye göre Ru’yetullah mümkündür; Allah’ın cennette mü’min kullarına kendisini göstermesi imkansız değildir. tazilah, Ashari’, God’s attiributes, divine unity tawhid, created Qur’an, be seen of god

COMPARISON OF COMPREHENSION OF DIVINE UNITY OF ASHARI AND MUTEZILITE The most basic doctrine the religion of Islam is divine unity (tawhid). Hence, Muslim thinkers in the first place contemplate heavily on expressions of God’s essence and divine unity. Methodically, there is two different school of thought within Islamic theology on the subject of divine unity which are Ahl-al-Sunnah and Mu’tazilite. The Mu’tazilite declare their opinions on divine unity, divine justice, advocating the good and forbidding the evil. None of the God’s attributes are like human beings'. God is unique and has attributes that no creature shares with Him. He has an eternal existence. Hence the Mu’tazilite prefer to interpret other private attributes of God. The Mu’tazilite claim that the Qur’an is created because the God’s speech (kelâm) is composed of sounds and letters. Considering that the passages in the Quran describes the essence of God to be regarded as metaphorical rather than literal, they believe that God cannot be seen in both of the worlds. Ash’arite confirm that the attributes of action are “negotional” (Selbiyye), while the attributes of essence are classed as “exiftential”. Ash’arite assert God’s speech is ancreated and is coeternal with His essence. God’s speech is inherend in Him, and in itsels, it’s neither a sensory (sound) nor a graficel trac that is manyfested in form of a letter. Ash’arite claim that the qur’anic lafziyya (enounciation) is created. Ash’arite believed that God willbeable to be seen in here after by believers to Him.
Keywords: İslam Dini; İslam Mezhepleri